Hello, Have a look at this page of the eBook: http://www.allaboutcircuits.com/vol_4/chpt_3/4.html You can also make a state table and compare. Bertus
Hello thisonedude I think it would be a lot of words trying to prove that (A XOR B)' = A' XOR B. Maybe if you look at the attached images you can find it. In these cases it would be faster to search in Google.com for answers. Among the many answers I found is that you look at the following link: http://pubs.sciepub.com/jcsa/1/1/3/ I hope you serve
(a xor b)' = (a xor b) xor 1 = a xor b xor 1 = a xor 1 xor b = (a xor 1) xor b = a' xor b. Edit: It was all in capitals. Forum software has changed it.
A XOR B is an inequality function. Hence (A XOR B)' - is equality function Hence (A XOR B) ' = (A' XOR B) = (A XOR B') This is not a proof but rationalized logic.